Fibrinogen-Aα THR312ALA Polymorphism is Associated to Chronic Thromboembolic Pulmonary Hypertension in Turkey - YILDIZELİ, BEDRETTİN (My University, 2023)
BACKGROUND: Chronic thromboembolic pulmonary hypertension is a condition that occurs after mechanical obstruction of the pulmonary arteries by thrombus. Since the frequency and demographics of chronic thromboembolic pulmonary hypertension differ between countries, it is thought that genetic factors may play a role in its development. The aim of this study is to reveal the status of VKORC1, CYP2C9*3, CYP2C9*7, and fibrinogen-Aα THR312ALA gene polymorphisms in chronic thromboembolic pulmonary hypertension patients in Turkey. METHODS: In this prospective cross-sectional study, a total of 46 chronic thromboembolic pulmonary hypertension patients and 106 healthy volunteers were included. Polymerase chain reaction-restriction fragment length polymorphism method was used to determine candidate gene polymorphisms for chronic thromboembolic pulmonary hypertension. The general population parameters of each locus were calculated, and the relationship between dominant, codominant, and recessive genotype models and chronic thromboembolic pulmonary hypertension was analyzed. RESULTS: For the fibrinogen-Aα gene, those with the THR/THR genotype were found to have a 13.51 (95% CI: 2.688-33.333) times less susceptibility rate to the disease than those with the ALA/THR genotype, the susceptibility of THR/ALA genotype to the disease was 5.026 (95% CI: 1.774-14.242) times more than those with ALA/ALA genotype. There was no difference between patient groups for VKORC1, CYP2C9*3 genes (P >.05). Since the CYP2C9*7 patient group was monomorphic for the ILE allele, the patient/control odds ratio and 95% CI could not be calculated. CONCLUSION: This study shows that there is an association between the fibrinogen-Aα gene ALA polymorphism at the amino acid position of 312 and the development of chronic thromboembolic pulmonary hypertension, but not between the CYP2C9 and VKORC1 gene polymorphisms.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine